33rd Joint Propulsion Conference and Exhibit 1997
DOI: 10.2514/6.1997-3016
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pulsed arc heater for a hypersonic high enthalpy wind tunnel

Abstract: A pulsed arc heater was designed and manufactured at Centrospazio to equip a new hypersonic high-enthalpy blow-down wind tunnel capable of producing flows with a specific total enthalpy up to 2.5 MJ/kg. The heater mainly consists of two coaxial electrodes, separated by a constrictor, and a plenum chamber. The flow is heated by an electric arc ignited between the electrodes and sustained by the discharge of a large capacitor bank. The plenum chamber allows the flow to reach thermo-chemical equilibrium before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Experimental tests have been carried out in Centrospazio high-enthalpy archeated tunnel (HEAT) [33,34] that is capable of producing Mach 6 flows with a specific total enthalpy up to 2.5 MJ/kg on an effective test section 60 mm in diameter, in the low to medium Reynolds number range (10 4 -10 6 ). The tunnel operates in a pulsed, quasi-steady mode, with running time ranging from 50 to 200 ms. HEAT facility mainly consists of an arc gas heater and a contoured expansion nozzle, installed in a vacuum chamber volume of 4.1 m 3 ; auxiliary systems are fitted to the arc heater to provide it with working fluid and energy.…”
Section: Shock-wave/boundary-layer Interactionmentioning
confidence: 99%
“…Experimental tests have been carried out in Centrospazio high-enthalpy archeated tunnel (HEAT) [33,34] that is capable of producing Mach 6 flows with a specific total enthalpy up to 2.5 MJ/kg on an effective test section 60 mm in diameter, in the low to medium Reynolds number range (10 4 -10 6 ). The tunnel operates in a pulsed, quasi-steady mode, with running time ranging from 50 to 200 ms. HEAT facility mainly consists of an arc gas heater and a contoured expansion nozzle, installed in a vacuum chamber volume of 4.1 m 3 ; auxiliary systems are fitted to the arc heater to provide it with working fluid and energy.…”
Section: Shock-wave/boundary-layer Interactionmentioning
confidence: 99%
“…The gas generator simulation code is based on a unsteady, lumped parameter formulation of the 2 mass, momentum and energy conservation equations for the gas, with the feeding valve opening schedule and the arc heat release as driving inputs. Previous analyses 1,5 showed that the code yields accurate predictions of the flowfield thermodynamic conditions, provided that the heat input W VI = η is correctly estimated in terms of the arc power, VI , and the energy transfer efficiency to gas, η . To this purpose, the arc voltage, V , has been correlated to current, I , electrode separation, s , and gas pressure in the constrictor, p , by means of 1,8,9 :…”
Section: The Gas Generator Flowmentioning
confidence: 99%
“…With reference to Fig. 1, the facility consists of an arc-heated gas generator 5 and an expansion nozzle 6 exhausting in a vacuum chamber, not shown in the picture. Air is injected from an upstream reservoir in the gas generator by two fastacting solenoid valves and heated as it flows through a constricted section by the electric arc established between the cylindrical cathode and the annular anode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental tests have been carried out in Centrospazio High-Enthalpy Archeated Tunnel (HEAT) [19,20] that is capable of producing Mach 6 flows with a specific total enthalpy up to 2.5MJ/kg on an effective test section 60mm in diameter, in the low to medium Reynolds number range (10 4 - 10 6 ). The tunnel operates in a pulsed, quasi-steady mode, with running time ranging from 50 to 200ms.…”
Section: Shock-wave/boundary-layer Interaction Experimentsmentioning
confidence: 99%